High-contrast photochromic Eu-doped K0.5Na0.5NbO3 ceramics with prominent pellucidity. Issue 14 (24th March 2021) - Zhou, Yang; Wang, Peng; Lin, Jinfeng; Lu, Qiling; Wu, Xiao; Gao, Min; Lin, Tengfei; Lin, Cong; Zheng, Xinghua
Abstract : Eu-doped K0.5 Na0.5 NbO3 pellucid ceramics, with light illumination-induced high-contrast photochromic behaviors of both optical transmittance and photoluminescence, exhibit potential in the application of optical data storage. Abstract : The Eu-doped K0.5 Na0.5 NbO3 pellucid ceramics were first prepared via a conventional solid-state reaction, and they exhibited light illumination-induced high-contrast photochromism of both optical transmittance and photoluminescence behaviors. Through thermal treatment, the optical performances could return to their initial states and displayed excellent reversibility. Eu 3+ ions were selected as the luminescent activator for detecting the local environment of the K0.5 Na0.5 NbO3 host. Meanwhile, the effects of the amount of Eu 3+ present on phase structures, microstructures, optical transmittance and photoluminescence intensities were systematically investigated. The results suggest that Eu-doped K0.5 Na0.5 NbO3 transparent ceramics possess multifunctionality including photochromism, photoluminescence and optical switching properties, and that they exhibit promising potential for non-destructive optical data storage application.